(untitled) (Horizon Multidisciplinary Scientific Journal, 2026)
The involvement of adolescents in negative subcultures and the problems of social adaptation are among the important socio-psychological processes that seriously affect personality development, behavior, and integration into society. The main factors contributing to these problems include weak family relationships, insufficient parental supervision, social isolation in the school environment, bullying, academic failure, and the strong influence of peer groups. Since adolescents at this stage have a strong need for belonging and acceptance, they may sometimes be drawn to negative subcultures. Information technologies and social networks also influence this process by accelerating the spread of risky behavioral patterns. Preventive measures play an important role in addressing these problems. Strengthening emotional support within the family, creating a healthy psychological environment at school, developing social skills, and organizing psychological services facilitate adolescents’ adaptation process. At the same time, the effective organization of leisure time and involvement in sports and social activities contribute to their positive development. As a result, the joint efforts of the family, school, and society play a key role in protecting adolescents from the influence of negative subcultures and in shaping them into socially healthy individuals.